PEMILAHAN SAMPAH MANDIRI DAN TEKNIK PEMBUATAN PUPUK ORGANIK CAIR DARI SAMPAH ORGANIK DI DESA SIDOREJO, KECAMATAN BANDONGAN, MAGELANG, JAWA TENGAH - Laeshita, Putri (Fakultas Pertanian_Universitas Tidar, 2022)
This community service aims to help train the community, especially housewives and farmer groups in Sidorejo Village in carrying out waste sorting independently and intensively as well as providing information on utilizing household organic waste as liquid organic fertilizer. This is because there is still no training on the importance of an effort to utilize waste, especially inorganic and organic waste produced by household waste. The methods used are lectures, questions and answers, forum discussions, and workshops on independent waste management training practices. The strategy for managing inorganic waste such as plastic can be done by recycling and depositing it in a waste bank to reduce environmental pollution. Inorganic waste is difficult to decompose by nature so that plastic waste can be used as handicraft products to reduce waste. Meanwhile, organic waste can be utilized by making liquid organic fertilizer based on EM4 bioactivator which can be applied to plants. With training and information on waste sorting independently and intensively, it is hoped that the community will be more concerned about the environment and be able to manage waste independently so that they can protect the environment and nature. Information in the form of processing organic waste into liquid fertilizer is expected to be continued into organic waste management into liquid fertilizer so that people can increase their income and become business opportunities that can improve people's welfare in the future.